Folklore hydronyms as an object of lexicography: some remarks and instructions regarding the structural and functional parameters of the dictionary description - Serdeha, Ruslan (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2025)
Folklore is an important component of national culture, and its verbal means significantly contributed to the formation of the literary variety of the Ukrainian language at certain stages of development. The study of the linguistic richness of oral folk literature reveals the diversity of the cultural heritage of our people and contributes to the strengthening of national consciousness. The language of folklore has long been in need of special purposeful lexicographic study. A significant place in the texts of oral folklore belongs to proper names, in particular hydronyms, which, in addition to a purely informative function, sometimes perform an artistic and figurative function in folklore texts. Hydronyms have long been in the field of linguists’ attention. The interest in their study is primarily because they are one of the oldest types of proper names. Today, Ukrainian scientists have compiled dictionaries that normalise the spelling of proper names of water bodies and lexicographical works that clarify the etymology of these names. However, the language of folklore in general and the hydronums used in it, in particular, have not yet been the subject of more or less systematic lexicographic description. The aim of the article is to present samples of lexicographic parameterisation of the names of water bodies functioning in the language of Ukrainian folklore. The material for the dictionary description was a variety of folklore material extracted from fairy tales, legends, and ballads on family and domestic themes, dumas, historical songs, and love songs. We have found that the most commonly used hydronyms in the texts of Ukrainian folklore are those used to name watercourses (rivers). There are also names of lakes, seas, sometimes ponds, and water crossings. Such names can directly correlate with reality or sometimes be a product of folk imagination. We have found out that invented names mostly function as part of pelagonyms. In making a lexicographic description of folklore hydronyms, we rely primarily on the traditional model of a dictionary entry. However, the area of explanation should reflect the specifics of these proper names - contain geospatial indicators, an indication of the type of water body, reflect the artistic originality of the hydronym used in folklore, and convey those additional shades (mythological, symbolic) that it acquires in the situation of specific word usage in a particular folklore text.